An honored vow ebook - Blair, Melissa (The Halfling Saga, 2025)
This thrilling romantasy about king's Blade, Keera, and her epic quest to avenge her lover, save her people, and bring down a tyrant king is the final installment of Melissa Blair's highly acclaimed series. The Halfling Saga showcases BIPOC and queer representation, love, passion, betrayal, magic, and great battles of the sword and the soul. "Your land is not the one you take; it is the one you die for." Keera has tried to keep her final promise to Brenna, the partner she was forced to kill to save a kingdom—but that promise has led to the most difficult struggles of her life. She's been at war with her worst self while battling King Damien for the freedom of the Halflings, and she's lost too many along the way. But when she finally breaks the last seal, unleashing the Fae magic that's been hidden away for hundreds of years, the conflict seems to be turning in the Halflings' favor. Meanwhile, Keera's discovery of a staggering secret about her lover and the kidnapping of one of her closest allies threatens to tip her back into darkness, but she has no time to rest. Opening the kingdom's magical seals has transformed Keera in ways even the wisest Fae elders could not have anticipated, and the return of an evil thought long vanquished throws their rescue plans into chaos. And with the kingdom's Halfling population suddenly posing a risk to the crown, the land is plunged into violence as the king begins a new blood purge. Keera and her allies must gather an army to meet Damien's forces in a final confrontation of epic—and tragic—proportions. The stunning conclusion of BookTok sensation Melissa Blair's epically romantic series will leave readers breathless as Keera fights for her land, her people, and the promise of a better world.